Tiktok & Law of Personal Branding for Product Marketing (Study on @Farhanbashel Tiktok Account) - Atikah Kanza Atsarina Hakim (Jurnal Multidisiplin Madani, 2023)
In line with the development of web 2.0 and the types of social media in the digital era, it cannot be separated from the development of cellular data connectivity which has become part of everyone's daily life, and has directly revolutionized the way people live, works, interact and socialize. The object of research in this writing is @farhanbashel TikTok account engaged in the lifestyle & fashion category. The analysis technique used is descriptive analysis with a qualitative approach. In this writing, researchers are trying to explore how TikTok accounts @farhanbashel build personal branding to create a public identity as a content creator in the fashion & lifestyle category on the TikTok platform, which in the end is considered to support product marketing activities in the form of endorsements and other forms of cooperation to market a product. Participatory culture in the digital era provides opportunities for social media users to create content according to their preferences, often referred to as user-generated content. Based on a statement from the account owner, Farhan Basel, these cooperation opportunities were formed and started solely from his TikTok account which was initiated during the early days of the COVID-19 pandemic, namely the beginning of 2020 with the initial intention only to fill free time. Indirectly, @farhanbashel TikTok account has carried out product marketing activities along with personal branding-building activities, as evidenced by the presence of values in the concept of eight laws of personal branding in the content shared